The problem: The y-intercept of the line tangent to y=(x4-2x2-8)ecosx2 at x=1 is (a) -15.499 (b) -25.999 (c) -41.448 (d) 15.449 (e) 25.99 To find the y-intercept I have to find the whole equation of the line y=f(1) m=f'(1) x=1 b=?? My problem is that I don't think I got the the derivative of f(x) right. I know you have to apply the product rule and the chain rule, but I don't know if the chain rule should be applied to ecosx2. I came up with this: (4x3-4x)ecosx2 + (x4-2x2-8)ecosx2(-sinx2)(2x) then y=-15.4487 m =15.1465 and b=-1.020 the intercept doesn't equal any of the given answers, but y= answer a. However, if I use f'(x)= (4x3-4x)ecosx2 + (x4-2x2-8)ecosx2, I get b=1. What did I do wrong?